Infarct Diameter for Predicting Cognitive Dysfunction in Ischemic Stroke Survivors in West Nusa Tenggara, Indonesia - Harahap, Herpan Syafii; Putri, Setyawati Asih; Indrayana, Yanna; Amin, Hasan; Mahardika, Fransisca Ika (Kesmas, 2022)
Cognitive dysfunction is an important consequence of ischemic stroke, which can progress in the first few years and is primarily determined by clinical factors. This study aimed to investigate the clinical determinants of cognitive dysfunction in stroke survivors in West Nusa Tenggara Province, Indonesia. This cross-sectional study assessed 255 ischemic stroke survivors with a mean age of 57.1±9.3 years old and 29–79 years old, recruited consecutively in three main hospitals in West Nusa Tenggara Province between March 2019 and October 2021. Categorical data collected included age, sex, education level, clinical determinants of ischemic stroke, and cognitive status of the patients. The association between the clinical determinants of ischemic stroke and the risk of cognitive dysfunction in patients was analyzed using logistic regression after adjusting for age, sex, and level of education. The final multiple logistic regression analysis models revealed infarct diameter as the only clinical determinant significantly associated with an increased risk of cognitive dysfunction (OR = 3.14;95% CI = 1.20–8.23). Thus, a larger infarct diameter is the only clinical determinant of cognitive dysfunction in ischemic stroke survivors in West Nusa Tenggara Province, Indonesia.